Anlotinib combined with transarterial chemoembolization for unresectable hepatocellular carcinoma associated with hepatitis B virus: a retrospective controlled study - Chen, Song; Cai, Hongjie; Wu, Zhiqiang; Tang, Shuangyan; Chen, Ludan; Wang, Fan; Zhuang, Wenquan; Guo, Wenbo (Frontiers in Oncology, 2023)
Purpose To investigate the efficacy and safety of combined treatment of anlotinib and transarterial chemoembolization (TACE) in patients with unresectable hepatocellular carcinoma (uHCC) associated with hepatitis B virus (HBV) infection. Methods We retrospectively collected the data of 96 uHCC patients associated with HBV infection who received either TACE only (TO group; n = 64) or anlotinib combined with TACE (TA group; n = 32) from January 2017 to January 2021. The primary endpoint was overall survival (OS). The secondary outcomes included progression-free survival (PFS), tumor response according to modified Response Evaluation Criteria in Solid Tumors (mRECIST) and RECIST 1.1, and adverse events (AEs). Results The median OS and median PFS were significantly longer in the TA group compared to the TO group (17.6 months vs. 9.4 months, p = 0.018; 6.7 months vs. 3.8 months, p = 0.003, respectively). In addition, the overall objective response rate (ORR) and disease control rate (DCR) numerically increased in the TA group (mRECIST, ORR 65.6% vs. 46.9%, p = 0.064, DCR 90.6% vs. 85.9%, p = 0.382; RECIST 1.1, ORR 46.9% vs. 15.6%, p = 0.001, DCR 90.6% vs. 85.9%, p = 0.382, respectively). It was worth noting that no treatment-related mortality occurred during the study. The most common AEs included elevated transaminases (56.3%), decreased appetite (46.9%), and abdominal pain (37.5%) in the TA group. Although the incidence rate of grade 3/4 AEs was higher in the TA group, all of them were controllable. Conclusions The combination of anlotinib and TACE has shown promising results in improving outcomes for patients with HBV-related uHCC, as compared to TACE monotherapy. In addition, this combination therapy has demonstrated a controllable safety profile. However, further validation is urgently needed through randomized controlled trials with large sample sizes.